2011
DOI: 10.1038/ijo.2011.27
|View full text |Cite
|
Sign up to set email alerts
|

Childhood overweight after establishment of the gut microbiota: the role of delivery mode, pre-pregnancy weight and early administration of antibiotics

Abstract: Objective: To investigate whether delivery mode (vaginal versus by caesarean section), maternal pre-pregnancy body mass index (BMI) and early exposure to antibiotics (o6 months of age) influence child's risk of overweight at age 7 years, hence supporting the hypotheses that environmental factors influencing the establishment and diversity of the gut microbiota are associated with later risk of overweight. Design: Longitudinal, prospective study with measure of exposures in infancy and follow-up at age 7 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
452
9
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 476 publications
(504 citation statements)
references
References 36 publications
27
452
9
12
Order By: Relevance
“…Decreased insulin sensivity following 1 week of vancomycin treatment was observed in humans following changes in gut microbiota and bile acids (34), whereas a retrospective study has reported increased adiposity following antibiotic treatment with vancomycin for infectious endocarditis (58). In contrast to these observations, exposure to antibiotics in early life among children of overweight mothers has been associated with a decreased risk of overweight in childhood (52) and studies of ob/ob, high-fat diet-fed and insulin-resistant mice have demonstrated improved glucose tolerance following antibiotic treatment (22,59). Collectively, these studies may suggest that exposure to antibiotics early in life on one hand has the potential to disturb a healthy gut microbiota but, on the other hand, also has the potential to modify a disturbed microbiota towards a healthier state.…”
Section: Type 2 Diabetes and Gut Microbiota: A Word Of Cautionmentioning
confidence: 47%
See 2 more Smart Citations
“…Decreased insulin sensivity following 1 week of vancomycin treatment was observed in humans following changes in gut microbiota and bile acids (34), whereas a retrospective study has reported increased adiposity following antibiotic treatment with vancomycin for infectious endocarditis (58). In contrast to these observations, exposure to antibiotics in early life among children of overweight mothers has been associated with a decreased risk of overweight in childhood (52) and studies of ob/ob, high-fat diet-fed and insulin-resistant mice have demonstrated improved glucose tolerance following antibiotic treatment (22,59). Collectively, these studies may suggest that exposure to antibiotics early in life on one hand has the potential to disturb a healthy gut microbiota but, on the other hand, also has the potential to modify a disturbed microbiota towards a healthier state.…”
Section: Type 2 Diabetes and Gut Microbiota: A Word Of Cautionmentioning
confidence: 47%
“…It has been speculated that the introduction of antibiotics in the early twentieth century may have contributed to the obesity epidemic and epidemiological studies have supported this notion as they have demonstrated that exposure to antibiotics in early childhood increases the risk of overweight in later childhood (52,53,54,55). Compared with children of normal-weight mothers not receiving antibiotics, the risk of overweight at age 7 years was increased by 1.5-fold among children receiving antibiotics during the first 6 months of life and born to normal-weight mothers (52).…”
Section: Type 2 Diabetes and Gut Microbiota: A Word Of Cautionmentioning
confidence: 87%
See 1 more Smart Citation
“…A longitudinal, prospective study in childhood revealed that a combination of early exposures, including delivery mode (vaginal v. by caesarean section), maternal pre-pregnancy BMI and antibiotics in infancy (less than 6 months of age), influences the risk of overweight in childhood, evaluated with a follow-up at age 7 years. This effect may potentially be explained by an impact on establishment and diversity of the microbiota (59) . Recently, Wang et al (60) identified a new direct link between gut flora-dependent metabolism of dietary phosphatidylcholine and CVD pathogenesis, which represents the leading cause of death and morbidity worldwide.…”
Section: Microbiota Epigenetics and Early Postnatal Nutritionmentioning
confidence: 99%
“…A similar bacterial profile have been found on intestinal microbiota in obese adults. 25 In this study, the exclusive breastfeeding less than four months was associated with EW. WHO recommends an exclusive breastfeeding until six months of years, since 2001.…”
Section: Discussionmentioning
confidence: 82%